Beyond the Driver Mutation: Immunotherapies in Gastrointestinal Stromal Tumors - Roulleaux Dugage, Matthieu; Jones, Robin Lewis; Trent, Jonathan; Champiat, Stéphane; Dumont, Sarah (Frontiers in Immunology, 2021)
Gastrointestinal stromal tumors (GISTs) are a subtype of soft tissue sarcoma (STS), and have become a concept of oncogenic addiction and targeted therapies.The large majority of these tumors develop after a mutation in KIT or platelet derived growth factor receptor α (PDGFRα), resulting in uncontrolled proliferation. GISTs are highly sensitive to imatinib. GISTs are immune infiltrated tumors with a predominance of tumor-associated macrophages (TAMs) and T-cells, including many CD8+ T-cells, whose numbers are prognostic. The genomic expression profile is that of an inhibited Th1 response and the presence of tertiary lymphoid structures and B cell signatures, which are known as predictive to response to ICI. However, the microtumoral environment has immunosuppressive attributes, with immunosuppressive M2 macrophages, overexpression of indoleamine 2,3-dioxygenase (IDO) or PD-L1, and loss of major histocompatibility complex type 1. In addition to inhibiting the KIT oncogene, imatinib appears to act by promoting cytotoxic T-cell activity, interacting with natural killer cells, and inhibiting the expression of PD-L1. Paradoxically, imatinib also appears to induce M2 polarization of macrophages. There have been few immunotherapy trials with anti-CTLA-4 or anti-PD-L1drugs and available clinical data are not very promising. Based on this comprehensive analysis of TME, we believe three immunotherapeutic strategies must be underlined in GIST. First, patients included in clinical trials must be better selected, based on the identified driver mutation (such as PDGFRα D842V mutation), the presence of tertiary lymphoid structures (TLS) or PD-L1 expression. Moreover, innovative immunotherapeutic agents also provide great interest in GIST, and there is a strong rationale for exploring IDO targeting after disease progression during imatinib therapy. Finally and most importantly, there is a strong rationale to combine of c-kit inhibition with immune checkpoint inhibitors.